Quality control circle: a tool for enhancing perceptions of patient safety culture among hospital staff in Chinese hospitals. (11th November 2019) - Zhang, Dan; Liao, Meixia; Zhou, Yiping; Liu, Tingfang
Abstract: Objective: To explore whether quality control circle (QCC) is associated with hospital staff's perceptions of patient safety culture (PSC). Design: A cross-sectional survey in 12 public hospitals from October to December 2018 and a longitudinal survey in one public hospital from November 2017 to November 2018. Setting: In 12 public hospitals from six provinces located in eastern, central and western of China, and one public hospital in eastern China. Participants: In total, 811 and 102 hospital staff participated in the cross-sectional survey and the longitudinal survey, respectively. These participants included doctors, nurses, medical technicians and administrative staff. Main Outcome Measures: Hospital staff's perceptions of PSC were measured by the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire. The association between QCC implementation and PSC was identified by univariate analysis and multiple linear regression analysis. Results: Univariate analysis showed that the staff from hospitals that had implemented QCC received significantly higher HSOPSC scores than those from hospitals where QCC had not been implemented (3.73 ± 0.61 vs. 3.57 ± 0.41, P  < 0.05). The QCC implementation was a significant predictor in the established multiple linear regression model. One year after QCC implementation, the hospital involved in the longitudinal survey scored higher in HSOPSC than before (3.75 ± 0.42 vs. 3.60 ± 0.36, P  < 0.001). Conclusions: QCC implementation was positively associated with PSC and the former could promote the establishment of the latter. It is suggested that QCC can play an active role in enhancing PSC so as to further improve patient safety management.